Corrosion inhibition effect of Elettaria cardamomum extract on mild steel in 3.5% NaCl medium. (2021) - Shyamvarnan, B.; Shanmugapriya, S.; Arockia Selvi, J.; Kamaraj, P.; Mohankumar, R.
Abstract: Ethanol extract of Elettaria cardamomum ( E. cardamomum ) of varying concentration ranging from 50 to 250 ppm was examined for its inhibition effect on mild steel corrosion in 3.5% NaCl medium. The corrosion rate and corrosion inhibition efficiency (IE) was investigated for about 1 and 7 days by weight loss method. The experimental results showed increase in IE with increase in concentration and decreased with the increase of immersion period, 73.5% maximum IE reached for 1 day and reduced to 54.1% for 7 days in the presence of 250 ppm E. cardamomum extract. IE was attributed due to adsorption of inhibitor on metal surface. Thermodynamic analysis indicates the adsorption to be a physisorption obeying Langmuir isotherm. Potentiodynamic polarization tests indicated that E.cardamomum extract acted as a cathodic inhibitor. Electrochemical impedance spectroscopy (EIS) showed that the corrosion inhibition process is governed by charge transfer resistance (Rct). The surface morphology of the inhibited and uninhibited mild steel specimen was studied by Scanning Electron Microscopy (SEM).